Patients with Chronic Hepatitis C - Who Should Not Be Treated? - Andreas Schüler; Michael Peter Manns (Canadian Journal of Gastroenterology)
The decision to treat a patient with chronic hepatitis C (CHC) is based on what is known about the risk factors for developing liver cirrhosis or hepatocellular carcinoma, as well as on conditions that contraindicate therapy or impair therapy effectiveness. Several factors, including age, treatment side effects, disease severity, concurrent diseases and life conditions, may render treatment decisions more difficult. This review focuses on identifying CHC patients who should not receive treatment.